Path to Green Prosperity : Evaluating the Interconnected Factors of Industry, Finance, and Energy in Developing Economies - Kumar, Arya; Dash, Mousumi; Kumar, Anuj; Hota, Sweta Leena; Mohanty, Debashisa; Vasudevan, Asokan (Prabandhan: Indian Journal of Management, 2024)
Purpose : The transition to renewable energy is essential for sustainable economic growth and environmental stability, and understanding the role of financial development (FD) in facilitating this shift is critical. This study investigated the impact of FD on renewable energy consumption across 101 economies, with a focus on the role of financial institutions. Design/Methodology/Approach : The study used a dynamic panel model to investigate the association between renewable energy consumption and FD in 101 economies. The model included these three variables to evaluate the influence of essential factors (market access, market efficiency, and financial institutions) on renewable energy increase. Findings : The findings revealed a positive correlation between renewable energy consumption in developed nations and FD, while the association was not statistically significant in developing economies. Financial institutions, especially banks, played a crucial role in enhancing renewable energy consumption, with factors such as accessibility, efficiency, and vertical cohesiveness of financial markets significantly influencing renewable energy adoption. The results also highlighted the practical implications of FD on renewable energy uptake, indicating that an approximate 0.01244 increase in renewable energy uptake corresponded to a per unit increase in the financial development index. Practical Implications : Governments could target establishing renewable energy funds and provide tax incentives to financial institutions to leverage financial institutions for renewable energy harnessing. Originality/Value : The research contributed to the existing literature by providing a comprehensive analysis of the relationship between FD and renewable energy adoption, emphasizing the crucial role of financial institutions in promoting sustainable energy practices.